The attitude of millennials towards the leadership of men and women in organizations - Diskienė, Danuta; Jaškevičiūtė, Vaida (Information & Media, 2017)
Modern organizations, in order to become and remain competitive, must be able to adapt to ongoing changes. One such change – an intensive change of labor market participants, during which the jobs of Generation X are taken up by the representatives of Generation Y, who grew up in a technological age. Generation Y possesses technological knowledge, ambition, a non-attachment to a single job and distinctive expectations toward leadership in the context of an organization. The article reveals the attitude shared by employees of the Generation Y regarding leadership in modern organizations, highlighting the gender aspect. On the background of the empirical study results, the perception of Gen Yers of managers and leadership characteristics of different genders were analyzed. Research findings disclosed that female leadership characteristics and behavior distinguished by respondents mostly coincided with the transformational leadership style, whereas male leadership peculiarities are more related to the transactional style. The study results also revealed that for most of the Generation Y, gender in management positions does not matter, also that the effectiveness of managers does not depend on the gender describing characteristics and behavior, but on how managers properly organize work, communicate with the staff and achieve set goals.
Keywords: ...